ShambaShield: Concept note - Vyas, Shalika; Chilambe, Pedro; Ghosh, Aniruddha; Timu, Anne; Sartas, Murat; Ramirez Villegas, Julian (2024)
ShambaShield is an integrated financial protection and advisory bundle designed to address the unique challenges faced by smallholder farmers in Kenya and other climate-vulnerable regions. By combining climate-risk assessed credit, digital agro-advisories, and financial literacy training, ShambaShield offers a comprehensive solution that empowers farmers to build resilience, improve productivity, and manage climate-related risks effectively. ShambaShield's innovation bundle aims to reach 500,000 smallholder farmers, at least 35% of whom are women, by the end of 2024. The proposed innovation package aims to expand the reach of the Shamba Shape Up (SSU) framework, focusing on an integrated and inclusive approach to financial and climate literacy for Kenyan farmers in maize-mixed systems. The cornerstone of this expansion is a package of a microfinance loan product and the widely recognized SSU TV series. This holistic approach provides (1) climate and financial information through SSU; (2) the financing required to enhance maize-mixed farming system resilience delivered by a financial institution and enabled by the climate-smart credit rating; and (3) the safety net provided by the insurance product (risk-contingent credit, RCC).